Decision making and experiences of young adults undergoing presymptomatic genetic testing for familial cancer: a longitudinal grounded theory study. (January 2018) - Godino, Lea; Jackson, Leigh; Turchetti, Daniela; Hennessy, Catherine; Skirton, Heather
Abstract Enabling informed choice is an essential component of care when offering young adults presymptomatic testing for a genetic condition. A systematic review on this topic revealed that many young adults grew up with little information regarding their genetic risk and that parents had applied pressure to them during the testing decision-making process. However, none of the studies retrieved were conducted in South European countries. To address this gap, we undertook a qualitative study based on grounded theory to explore the psychosocial implications of presymptomatic testing for hereditary cancer in Italian young adults aged 18–30 years. Interviews were conducted on three occasions: 1 month before counselling, and 2 weeks and 6 months after results. Data were coded and grouped under themes. A total of 42 interviews were conducted. Four themes emerged: knowledge, genetic counselling process, decision making and dealing with test results. Although participants grew up with little or no information about their genetic risk, none expressed regret at having the test at a young age. Pre-test counselling was appreciated as a source of information, rather than support for decision making. Decisions were often made autonomously and sometimes conflicted with parents' wishes. Participants reported no changes in health behaviours after testing. This evidence highlights the need for a comprehensive, longitudinal counselling process with appropriate timing and setting, which supports 'parent-to-offspring' risk communication first and decision making by young adults about presymptomatic testing and risk management afterwards. In conclusion, it is clear that counselling approaches for presymptomatic testing may require modification both for young adults and their parents.